Thermoplastic resin composition
A thermoplastic resin composition with orthophosphoric acid ester compounds and phenolic compounds enhances heat resistance and flame retardancy, addressing yellowing and resin deterioration issues in high temperature and humidity environments.
Patent Information
- Application Number
- JP2020154547
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-15
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2040-09-15
AI Technical Summary
Existing thermoplastic resin compositions used in electrical and electronic equipment, automobile parts, and mechanical parts face issues with yellowing and resin deterioration in high temperature and high humidity environments, lacking effective flame retardancy and heat resistance.
A thermoplastic resin composition is developed by blending appropriate amounts of orthophosphoric acid ester compounds, phenolic compounds, and flame retardants with polycarbonate resin and polyarylate resin to enhance heat resistance, flame retardancy, and prevent yellowing and resin deterioration.
The composition effectively prevents yellowing during molding retention and resin deterioration in high temperature and high humidity conditions while improving flame retardancy and maintaining mechanical properties.
Smart Images

Figure 0007613856000001 
Figure 0007613856000002 
Figure 0007613856000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition, more specifically, to a thermoplastic resin composition in which yellowing during molding retention, resin deterioration under high temperature and high humidity environments, and flame retardancy are improved by blending an orthophosphate compound, a phenolic compound, and a flame retardant in appropriate amounts with a resin component consisting of a polycarbonate resin and a polyarylate resin. [Background technology]
[0002] Compositions consisting of polycarbonate resin, polyarylate resin and flame retardant have excellent properties such as heat resistance, mechanical strength, dimensional stability and flame retardancy, and molded articles thereof are widely used in the fields of electric / electronic device parts, automobile parts, machine parts, etc. (See Patent Documents 1 and 2.) However, there is no disclosure about the obtainment of a composition capable of suppressing resin deterioration in a high-temperature and high-humidity environment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2009-256429 A [Patent Document 2] JP 2009-275062 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide a thermoplastic resin composition which is excellent in heat resistance and flame retardancy, does not discolor during retention in molding, and further, is inhibited from deteriorating in a high-temperature, high-humidity environment. [Means for solving the problem]
[0005] As a result of intensive studies to achieve the above object, the present inventors have found that by appropriately blending a positive phosphate ester compound, a phenolic compound, and a flame retardant into a resin composition composed of a polycarbonate resin and a polyarylate resin, a thermoplastic resin composition excellent in heat resistance and flame retardancy and improved in yellowing during molding residence time and resin deterioration under a high-temperature and high-humidity environment can be obtained. Further intensive studies have been carried out to complete the present invention.
[0006] Hereinafter, the present invention will be specifically described.
[0007] <Component A: Polycarbonate resin> The polycarbonate resin used in the present invention is obtained by reacting a dihydric phenol with a carbonate precursor. Examples of the reaction method include an interfacial polymerization method, a melt transesterification method, a solid-phase transesterification method of a carbonate prepolymer, and a ring-opening polymerization method of a cyclic carbonate compound.
[0008] Representative examples of the dihydric phenols used herein include hydroquinone, resorcinol, 4,4'-biphenol, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxyphenyl)pentane, 4,4'-(p-phenylene) Examples of the dihydric phenol include 4,4'-(m-phenylenediisopropylidene)diphenol, 1,1-bis(4-hydroxyphenyl)-4-isopropylcyclohexane, bis(4-hydroxyphenyl)oxide, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfoxide, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, bis(4-hydroxyphenyl)ester, bis(4-hydroxy-3-methylphenyl)sulfide, 9,9-bis(4-hydroxyphenyl)fluorene, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene. The preferred dihydric phenol is a bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred from the viewpoint of impact resistance and is widely used.
[0009] In the present invention, in addition to bisphenol A-based polycarbonate resins, which are general-purpose polycarbonate resins, it is possible to use special polycarbonate resins produced using other dihydric phenols as the A component.
[0010] For example, polycarbonate resins (homopolymers or copolymers) using 4,4'-(m-phenylenediisopropylidene)diphenol (hereinafter sometimes abbreviated as "BPM"), 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (hereinafter sometimes abbreviated as "Bis-TMC"), 9,9-bis(4-hydroxyphenyl)fluorene and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (hereinafter sometimes abbreviated as "BCF") as part or all of the dihydric phenol components are suitable for applications where dimensional changes due to water absorption and dimensional stability are particularly demanding. These dihydric phenols other than BPA are preferably used in an amount of 5 mol% or more, particularly 10 mol% or more, of the total dihydric phenol components constituting the polycarbonate resin.
[0011] In particular, when high rigidity and better hydrolysis resistance are required, it is particularly suitable that the component A constituting the resin composition is a copolymer polycarbonate resin of the following (1) to (3). (1) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and BCF is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %). (2) A copolymerized polycarbonate resin in which, relative to 100 mol % of a dihydric phenol component constituting the polycarbonate resin, BPA is 10 to 95 mol % (more preferably 50 to 90 mol %, and even more preferably 60 to 85 mol %) and BCF is 5 to 90 mol % (more preferably 10 to 50 mol %, and even more preferably 15 to 40 mol %). (3) A copolymer polycarbonate resin in which, relative to 100 mol % of the dihydric phenol component constituting the polycarbonate resin, BPM is 20 to 80 mol % (more preferably 40 to 75 mol %, and even more preferably 45 to 65 mol %) and Bis-TMC is 20 to 80 mol % (more preferably 25 to 60 mol %, and even more preferably 35 to 55 mol %).
[0012] These special polycarbonate resins may be used alone or in a suitable mixture of two or more. They may also be used in a mixture with the commonly used bisphenol A polycarbonate resin. The production methods and properties of these special polycarbonate resins are described in detail in, for example, JP-A-6-172508, JP-A-8-27370, JP-A-2001-55435, and JP-A-2002-117580.
[0013] Among the various polycarbonate resins mentioned above, those in which the copolymer composition and the like are adjusted to bring the water absorption rate and Tg (glass transition temperature) into the ranges described below have good hydrolysis resistance of the polymer itself and are also remarkably excellent in terms of low warpage after molding, and are therefore particularly suitable in fields where dimensional stability is required. (i) a polycarbonate resin having a water absorption rate of 0.05 to 0.15%, preferably 0.06 to 0.13%, and a Tg of 120 to 180° C.; or (ii) A polycarbonate resin having a Tg of 160 to 250° C., preferably 170 to 230° C., and a water absorption of 0.10 to 0.30%, preferably 0.13 to 0.30%, and more preferably 0.14 to 0.27%.
[0014] Here, the water absorption rate of the polycarbonate resin is a value measured by using a disk-shaped test piece having a diameter of 45 mm and a thickness of 3.0 mm and immersing it in water at 23°C for 24 hours in accordance with ISO62-1980, and measuring the moisture content. Also, Tg (glass transition temperature) is a value determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7121.
[0015] The carbonate precursor may be a carbonyl halide, a carbonic acid diester or a haloformate, and specific examples thereof include phosgene, diphenyl carbonate or a dihaloformate of a dihydric phenol.
[0016] When the dihydric phenol and carbonate precursor are used to produce a polycarbonate resin by interfacial polymerization, a catalyst, a terminal terminator, an antioxidant for preventing oxidation of the dihydric phenol, etc. may be used as necessary. The polycarbonate resin of the present invention includes a branched polycarbonate resin copolymerized with a trifunctional or higher polyfunctional aromatic compound, a polyester carbonate resin copolymerized with an aromatic or aliphatic (including alicyclic) bifunctional carboxylic acid, a copolymerized polycarbonate resin copolymerized with a bifunctional alcohol (including alicyclic), and a polyester carbonate resin copolymerized with such a bifunctional carboxylic acid and a bifunctional alcohol. The polycarbonate resin may also be a mixture of two or more of the obtained polycarbonate resins.
[0017] The branched polycarbonate resin can impart drip prevention properties to the resin composition of the present invention. Examples of trifunctional or higher polyfunctional aromatic compounds used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0018] The structural unit derived from a polyfunctional aromatic compound in the branched polycarbonate resin is preferably 0.01 to 1 mol%, more preferably 0.05 to 0.9 mol%, and even more preferably 0.05 to 0.8 mol% out of the total 100 mol% of the structural unit derived from a dihydric phenol and the structural unit derived from the polyfunctional aromatic compound. In particular, in the case of the melt transesterification method, a branched structural unit may be generated as a side reaction, and the amount of such a branched structural unit is preferably 0.001 to 1 mol%, more preferably 0.005 to 0.9 mol%, and even more preferably 0.01 to 0.8 mol% out of the total 100 mol% of the structural unit derived from the dihydric phenol. The proportion of such a branched structure is 1 It can be calculated by H-NMR measurement.
[0019] The aliphatic difunctional carboxylic acid is preferably an α,ω-dicarboxylic acid. Examples of the aliphatic difunctional carboxylic acid include linear saturated aliphatic dicarboxylic acids such as sebacic acid (decanedioic acid), dodecanedioic acid, tetradecanedioic acid, octadecanedioic acid, and icosane diacid, and alicyclic dicarboxylic acids such as cyclohexane dicarboxylic acid. The bifunctional alcohol is more preferably an alicyclic diol, such as cyclohexane dimethanol, cyclohexane diol, and tricyclodecane dimethanol.
[0020] The reaction modes of the method for producing the polycarbonate resin of the present invention, such as the interfacial polymerization method, the melt transesterification method, the carbonate prepolymer solid-phase transesterification method, and the ring-opening polymerization method of a cyclic carbonate compound, are well known in various literatures and patent publications.
[0021] In producing the thermoplastic resin composition of the present invention, the viscosity average molecular weight (M) of the polycarbonate resin is not particularly limited, but is preferably 1.8×10 4 ~4.0×10 4 and more preferably 2.0×10 4 ~3.5×10 4, and more preferably 2.2×10 4 ~3.0×10 4 The viscosity average molecular weight is 1.8 × 10 4 Polycarbonate resins with a viscosity average molecular weight of less than 4.0×10 may not provide good mechanical properties. 4 Resin compositions obtained from polycarbonate resins exceeding this limit are inferior in terms of flowability during injection molding and therefore are inferior in versatility.
[0022] The polycarbonate resin may be a mixture of polycarbonate resins having a viscosity average molecular weight outside the above range. 4 ) the entropy elasticity of the resin is improved. As a result, good molding processability is exhibited in gas-assisted molding and foam molding, which are sometimes used when molding reinforced resin materials into structural members. Such improvement in molding processability is even better than that of the branched polycarbonate resin. In a more preferred embodiment, component A has a viscosity average molecular weight of 7×10 4 ~3×10 5 Polycarbonate resin A-1-1 component) and viscosity average molecular weight 1 × 10 4 ~3×10 4 The aromatic polycarbonate resin (A-1-2 component) has a viscosity average molecular weight of 1.6×10 4 ~3.5×10 4 A polycarbonate resin (A-1 component) (hereinafter, sometimes referred to as a "polycarbonate resin containing a high molecular weight component") can also be used.
[0023] In the polycarbonate resin containing a high molecular weight component (A-1 component), the molecular weight of the A-1-1 component is 7×10 4 ~2×10 5 is preferable, and more preferably 8×10 4 ~2×10 5 , and more preferably 1×10 5 ~2×10 5 , particularly preferably 1×10 5 ~1.6×10 5The molecular weight of component A-1-1-2 is 1×10 4 ~2.5×10 4 is preferable, and more preferably 1.1×10 4 ~2.4×10 4 , and more preferably 1.2×10 4 ~2.4×10 4 , and particularly preferably 1.2×10 4 ~2.3×10 4 It is.
[0024] The high molecular weight component-containing polycarbonate resin (A-1 component) can be obtained by mixing the A-1-1 component and the A-1-2 component in various ratios and adjusting to satisfy a predetermined molecular weight range. Preferably, the A-1-1 component is 2 to 40% by weight, more preferably 3 to 30% by weight, even more preferably 4 to 20% by weight, and particularly preferably 5 to 20% by weight, of 100% by weight of the A-1 component.
[0025] Methods for preparing component A-1 include (1) independently polymerizing components A-1-1 and A-1-2 and mixing them, (2) using a method for producing an aromatic polycarbonate resin that shows multiple polymer peaks in a molecular weight distribution chart by GPC method, in the same system, as typified by the method shown in JP-A-5-306336, to produce such an aromatic polycarbonate resin so as to satisfy the conditions of component A-1 of the present invention, and (3) mixing an aromatic polycarbonate resin obtained by such a production method (production method (2)) with components A-1-1 and / or A-1-2 that have been produced separately.
[0026] The viscosity average molecular weight in the present invention is calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution of 0.7 g of polycarbonate resin in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) and calculate the viscosity average molecular weight M using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7
[0027] The viscosity average molecular weight of the polycarbonate resin in the thermoplastic resin composition of the present invention is calculated as follows. That is, the composition is mixed with methylene chloride in an amount 20 to 30 times by weight, and the soluble matter in the composition is dissolved. The soluble matter is collected by filtration through Celite. The solvent in the resulting solution is then removed. The solid after the solvent removal is thoroughly dried to obtain a solid of components that dissolve in methylene chloride. 0.7 g of the solid is dissolved in 100 ml of methylene chloride, and the specific viscosity at 20°C is determined in the same manner as above, and the viscosity average molecular weight M is calculated from the specific viscosity in the same manner as above.
[0028] The polycarbonate resin of the present invention may be a polycarbonate-polydiorganosiloxane copolymer resin. The polycarbonate-polydiorganosiloxane copolymer resin is preferably a copolymer resin containing a dihydric phenol unit represented by the following general formula (1) and a hydroxyaryl-terminated polydiorganosiloxane unit represented by the following general formula (3).
[0029] [ka]
[0030] [In the above general formula (1), R 1 and R 2each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 14 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of each, they may be the same or different, a and b each represent an integer of 1 to 4, and W represents a single bond or at least one group selected from the group consisting of groups represented by the following general formula (2):
[0031] [ka]
[0032] (In the above general formula (2), R 11 ,R 12 ,R 13 ,R 14 ,R 15 ,R 16 ,R 17 and R 18 each independently represents a group selected from the group consisting of a hydrogen atom, an alkyl group having 1 to 18 carbon atoms, an aryl group having 6 to 14 carbon atoms, and an aralkyl group having 7 to 20 carbon atoms; R 19 and R 20 each independently represents a group selected from the group consisting of a hydrogen atom, a halogen atom, an alkyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, a cycloalkyl group having 6 to 20 carbon atoms, a cycloalkoxy group having 6 to 20 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, an aryl group having 6 to 14 carbon atoms, an aryloxy group having 6 to 10 carbon atoms, an aralkyl group having 7 to 20 carbon atoms, an aralkyloxy group having 7 to 20 carbon atoms, a nitro group, an aldehyde group, a cyano group, and a carboxyl group, and when there are a plurality of groups, they may be the same or different, c is an integer from 1 to 10, and d is an integer from 4 to 7.)
[0033] [ka]
[0034] [In the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms; R 9 and R 10 are each independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms, e and f are each an integer of 1 to 4, p is a natural number, q is 0 or a natural number, and p+q is a natural number of 4 or more and 150 or less, and X is a divalent aliphatic group having 2 to 8 carbon atoms.]
[0035] Examples of the dihydric phenol (I) from which the carbonate structural unit represented by the general formula (1) is derived include 4,4'-dihydroxybiphenyl, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 2,2-bis(4-hydroxy-3 ,3'-biphenyl)propane, 2,2-bis(4-hydroxy-3-isopropylphenyl)propane, 2,2-bis(3-t-butyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxyphenyl)butane, 2,2-bis(4-hydroxyphenyl)octane, 2,2-bis(3-bromo-4-hydroxyphenyl)propane, 2,2-bis(3,5-dimethyl-4-hydroxyphenyl)propane, 2,2-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 1,1-bis(3-cyclohexyl-4-hydroxyphenyl)propane, 4,4'-Dihydroxydiphenyl ether, 4,4'-Dihydroxy-3,3'-dimethyldiphenyl ether, 4,4'-Sulfonyldiphenol, 4,4'-Dihydroxydiphenyl sulfoxide , 4,4'-dihydroxydiphenyl sulfide, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2'-diphenyl-4,4'-sulfonyldiphenol, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfoxide, 4,4'-dihydroxy-3,3'-diphenyldiphenyl sulfide, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,Examples of such benzene derivatives include 4-bis{2-(4-hydroxyphenyl)propyl}benzene, 1,4-bis(4-hydroxyphenyl)cyclohexane, 1,3-bis(4-hydroxyphenyl)cyclohexane, 4,8-bis(4-hydroxyphenyl)tricyclo[5.2.1.02,6]decane, 4,4'-(1,3-adamantanediyl)diphenol, and 1,3-bis(4-hydroxyphenyl)-5,7-dimethyladamantane.
[0036] Among these, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-sulfonyldiphenol, 2,2'-dimethyl-4,4'-sulfonyldiphenol, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,3-bis{2-(4-hydroxyphenyl)propyl}benzene, and 1,4-bis{2-(4-hydroxyphenyl)propyl}benzene are preferred, and 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane (BPZ), 4,4'-sulfonyldiphenol, and 9,9-bis(4-hydroxy-3-methylphenyl)fluorene are particularly preferred. Among these, 2,2-bis(4-hydroxyphenyl)propane, which has excellent strength and good durability, is most suitable. These may be used alone or in combination of two or more kinds.
[0037] In the carbonate structural unit represented by the above general formula (3), R 3 , R 4 , R 5 , R 6 , R 7 and R 8 are each independently preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, and are particularly preferably a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a phenyl group. 9 and R 10are each independently preferably a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, and particularly preferably a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. As the dihydroxyaryl-terminated polydiorganosiloxane (II) from which the carbonate structural unit represented by the above general formula (3) is derived, for example, a compound represented by the following general formula (I) is suitably used.
[0038] [ka]
[0039] p+q is preferably 4-120, more preferably 30-120, further preferably 30-100, and most preferably 30-60.
[0040] Next, a method for producing the above-mentioned preferred polycarbonate-polydiorganosiloxane copolymer resin will be described below. In advance, in a mixed solution of a water-insoluble organic solvent and an aqueous alkali solution, a mixed solution of chloroformate compounds containing a chloroformate of dihydric phenol (I) and / or a carbonate oligomer of dihydric phenol (I) having a terminal chloroformate group is prepared by reacting dihydric phenol (I) with a chloroformate-forming compound such as phosgene or a chloroformate of dihydric phenol (I) in a mixed solution of the water-insoluble organic solvent and the aqueous alkali solution. Phosgene is preferred as the chloroformate-forming compound.
[0041] In producing a chloroformate compound from a dihydric phenol (I), the entire amount of the dihydric phenol (I) from which the carbonate structural unit represented by the above general formula (1) is derived may be converted into a chloroformate compound at once, or a part of it may be added as a post-added monomer to the subsequent interfacial polycondensation reaction as a reaction raw material. The post-added monomer is added to rapidly advance the subsequent polycondensation reaction, and it is not necessary to add it if it is not necessary. The method of this chloroformate compound production reaction is not particularly limited, but it is usually preferable to carry out the reaction in a solvent in the presence of an acid binder. Furthermore, if desired, a small amount of an antioxidant such as sodium sulfite and hydrosulfide may be added, and it is preferable to add it. The proportion of the chloroformate-forming compound used may be appropriately adjusted in consideration of the stoichiometric ratio (equivalent) of the reaction. In addition, when phosgene, which is a suitable chloroformate-forming compound, is used, a method of blowing gasified phosgene into the reaction system can be preferably adopted.
[0042] The acid binder may be, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, an alkali metal carbonate such as sodium carbonate or potassium carbonate, or an organic base such as pyridine, or a mixture thereof. The proportion of the acid binder used may be appropriately determined in consideration of the stoichiometric ratio (equivalent) of the reaction, as described above. Specifically, it is preferable to use 2 equivalents or a slightly excess amount of the acid binder per mole of the dihydric phenol (I) used to form the chloroformate compound of the dihydric phenol (I) (usually 1 mole corresponds to 2 equivalents).
[0043] As the solvent, a solvent inert to various reactions, such as those used in the production of known polycarbonates, may be used alone or as a mixture of solvents.Typical examples include hydrocarbon solvents such as xylene, and halogenated hydrocarbon solvents such as methylene chloride and chlorobenzene.In particular, halogenated hydrocarbon solvents such as methylene chloride are preferably used.
[0044] The pressure in the reaction for producing the chloroformate compound is not particularly limited, and may be normal pressure, elevated pressure, or reduced pressure, but it is usually advantageous to carry out the reaction under normal pressure. The reaction temperature is selected from the range of -20 to 50°C, and since the reaction often generates heat, it is preferable to cool the reaction with water or ice. The reaction time depends on other conditions and cannot be generally specified, but is usually carried out for 0.2 to 10 hours. The pH range in the reaction for producing the chloroformate compound can be determined using known interfacial reaction conditions, and the pH is usually adjusted to 10 or more.
[0045] In producing the polycarbonate-polydiorganosiloxane copolymer resin of the present invention, after preparing a mixed solution of chloroformate compounds containing a chloroformate of dihydric phenol (I) and a carbonate oligomer of dihydric phenol (I) having terminal chloroformate groups in this manner, the mixed solution is stirred and dihydroxyaryl-terminated polydiorganosiloxane (II) which derives the carbonate structural unit represented by general formula (3) is added at a rate of 0.01 mol / min or less per mol of the dihydric phenol (I) charged in preparing the mixed solution, thereby causing interfacial polycondensation of the dihydroxyaryl-terminated polydiorganosiloxane (II) and the chloroformate compound, thereby obtaining a polycarbonate-polydiorganosiloxane copolymer resin.
[0046] The polycarbonate-polydiorganosiloxane copolymer resin can be made into a branched polycarbonate-polydiorganosiloxane copolymer resin by using a branching agent in combination with a dihydric phenol compound. Examples of the polyfunctional aromatic compounds having three or more functionalities used in such branched polycarbonate resins include phloroglucin, phloroglucide, 4,6-dimethyl-2,4,6-tris(4-hydroxyphenyl)heptene-2,2,4,6-trimethyl-2,4,6-tris(4-hydroxyphenyl)heptane, 1,3,5-tris(4-hydroxyphenyl)benzene, 1,1,1-tris(4-hydroxyphenyl)ethane, 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane, 2,6-bis(2-hydroxy-5-methylbenzyl)-4-methylphenol, 4-{4-[1,1-bis(4- Examples of the trisphenols include trisphenols such as 1,4-dimethylbenzylphenol, tetra(4-hydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)ketone, 1,4-bis(4,4-dihydroxytriphenylmethyl)benzene, trimellitic acid, pyromellitic acid, benzophenonetetracarboxylic acid, and acid chlorides thereof. Among these, 1,1,1-tris(4-hydroxyphenyl)ethane and 1,1,1-tris(3,5-dimethyl-4-hydroxyphenyl)ethane are preferred, and 1,1,1-tris(4-hydroxyphenyl)ethane is particularly preferred.
[0047] The method for producing such a branched polycarbonate-polydiorganosiloxane copolymer resin may be a method in which a branching agent is contained in the mixed solution during the formation reaction of the chloroformate compound, or a method in which a branching agent is added during the interfacial polycondensation reaction after the formation reaction. The proportion of carbonate constituent units derived from the branching agent is preferably 0.005 to 1.5 mol %, more preferably 0.01 to 1.2 mol %, and particularly preferably 0.05 to 1.0 mol %, based on the total amount of carbonate constituent units constituting the copolymer resin. The amount of branched structures is 1 It can be calculated by H-NMR measurement.
[0048] The pressure in the system in the polycondensation reaction can be any of reduced pressure, normal pressure, or increased pressure, but usually, it can be preferably carried out at normal pressure or about the autogenous pressure of the reaction system. The reaction temperature is selected from the range of -20 to 50 °C. Since heat is usually generated during polymerization, it is desirable to carry out water cooling or ice cooling. The reaction time varies depending on other conditions such as the reaction temperature and cannot be generally specified, but usually, it is carried out for 0.5 to 10 hours. Optionally, the obtained polycarbonate-polydiorganosiloxane copolymer resin is appropriately subjected to physical treatment (mixing, fractionation, etc.) and / or chemical treatment (polymer reaction, cross-linking treatment, partial decomposition treatment, etc.) to obtain a polycarbonate-polydiorganosiloxane copolymer resin with a desired reduced viscosity SP / c]. The obtained reaction product (crude product) can be recovered as a polycarbonate-polydiorganosiloxane copolymer resin with a desired purity (degree of purification) by subjecting it to various post-treatments such as known separation and purification methods.
[0049] The content of the polydiorganosiloxane block represented by the following general formula (4) contained in the above general formula (3) is preferably 1.0 to 10.0% by weight, more preferably 1.0 to 8.0% by weight, still more preferably 1.0 to 5.0% by weight, and most preferably 1.0 to 3.0% by weight based on the total weight of the polycarbonate resin composition.
[0050] [Chemical formula]
[0051] (In the above general formula (4), R 3 , R 4 , R 5 , R 6 , R 7 , and R 8 are each independently a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a substituted or unsubstituted aryl group having 6 to 12 carbon atoms, p is a natural number, q is 0 or a natural number, and p + q is a natural number of 4 or more and 150 or less.)
[0052] <Component B: Polyarylate resin> The polyarylate resin used as component B of the present invention may be obtained by a conventional method from a dihydric phenol or its derivative and an aromatic dicarboxylic acid or its derivative. The dihydric phenol used here may be, for example, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4-dihydroxy-biphenyl, bis(4-hydroxyphenyl)methane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-(4-hydroxy-3-methylphenyl)propane, 4,4'-dihydroxydiphenylsulfone, 4,4'-dihydroxydiphenylether, 4,4'-dihydroxydiphenylsulfide, etc., and two or more of them may be used in combination.
[0053] The aromatic dicarboxylic acid may be any one that reacts with a dihydric phenol to give a satisfactory polymer, and may be used alone or in combination of two or more. Preferred aromatic dicarboxylic acids include terephthalic acid and isophthalic acid, and their mixtures are particularly preferred in terms of melt processability and overall performance. The mixing ratio of these mixtures does not need to be particularly limited, but terephthalic acid / isophthalic acid=9 / 1 to 1 / 9 (molar ratio) is preferred, and 7 / 3 to 3 / 7 (molar ratio) is particularly preferred in terms of the balance between melt processability and performance.
[0054] The polyarylate resin used as component B of the present invention is preferably a copolymer containing a polymerization unit represented by any one of the following general formulas (5) to (7). When a polyarylate resin not containing this structure is used, the impact resistance may decrease.
[0055] [ka]
[0056] [In the above general formula (5), l, m, and n are positive integers satisfying l + m + n = 100, l:n = 50:50 to 70:30, and (l + n):m = 75:25 to 40:60.]
[0057]
Chemical formula
[0058] [In the above general formula (6), m and n are positive integers, and m / n = 8 / 2 to 2 / 8.]
[0059]
Chemical formula
[0060] [In the above general formula (7), n is a positive integer.]
[0061] The content of the polyarylate resin used as the component B of the present invention is 1 to 99 parts by weight, preferably 10 to 50 parts by weight, more preferably 20 to 40 parts by weight, in 100 parts by weight of the resin component composed of the component A and the component B. When the content of the component B exceeds 99 parts by weight, yellowing during molding residence time becomes large. When it is less than 1 part by weight, excellent heat resistance cannot be obtained, and further resin deterioration under a high-temperature and high-humidity environment becomes large.
[0062] Examples of commercially available polyarylate resins include "U-100" (trade name), "M-2040" (trade name), "M-2040H" (trade name), etc. of Unitika Ltd.
[0063] <Component C: Orthophosphate ester compound> The content of the orthophosphate ester compound used as Component C of the present invention is 0.001 to 2 parts by weight, preferably 0.005 to 0.5 parts by weight, more preferably 0.01 to 0.1 parts by weight, based on 100 parts by weight of the resin component composed of Component A and Component B. When the content of Component C is less than 0.001 part by weight, yellowing during molding residence time becomes significant, and when it exceeds 2 parts by weight, resin deterioration in a high-temperature and high-humidity environment becomes significant. In addition, when a phosphate ester compound other than the orthophosphate ester compound is used as Component C, resin deterioration in a high-temperature and high-humidity environment becomes significant.
[0064] The type of the orthophosphate ester compound is not particularly limited, but an orthophosphate ester compound having a number average molecular weight of 50 to 600 is preferred. The number average molecular weight is more preferably 100 to 550, and even more preferably 140 to 500. Further, the melting point of the orthophosphate ester compound is preferably 30 to 80°C. An orthophosphate ester compound satisfying these regulations may particularly exhibit the effects of suppressing yellowing during molding residence time and suppressing resin deterioration in a high-temperature and high-humidity environment.
[0065] Specific examples of the orthophosphate ester compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, etc., and triphenyl phosphate and trimethyl phosphate are preferred.
[0066] <Component D: Phenolic compound> The content of the phenolic compound used as component D of the present invention is 0.001 to 2 parts by weight, preferably 0.01 to 0.5 parts by weight, and more preferably 0.03 to 0.08 parts by weight, relative to 100 parts by weight of the resin component consisting of components A and B. If the content of component D is less than 0.001 part by weight, the resin deteriorates significantly in a high-temperature, high-humidity environment, and if it exceeds 2 parts by weight, yellowing during retention in molding increases.
[0067] The type of phenolic compound used as component D of the present invention is not particularly limited, but when a hindered phenolic antioxidant or a phenolic compound having a melting point of 30 to 70° C. is used, the effect of suppressing yellowing during molding retention and suppressing resin deterioration under high temperature and high humidity environments may be particularly exhibited. Examples of phenolic antioxidants include α-tocopherol, butyl hydroxytoluene, sinapyl alcohol, vitamin E, n-octadecyl-β-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate, 2-tert-butyl-6-(3'-tert-butyl-5'-methyl-2'-hydroxybenzyl)-4-methylphenyl acrylate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di- tert-Butyl-4-hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 2,2'-dimethylene-bis(6-α-methyl-benzyl-p-cresol) 2,2'-ethylidene -Bis(4,6-di-tert-butylphenol), 2,2'-butylidene-bis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol-N-bis-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2-tert t-Butyl-4-methyl 6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl] terephthalate, 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, 4,4'-thiobis(6-tert-butyl-m-cresol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl) sulfide, 4,4'-dithiobis(2,6-di-tert-butylphenol), 4,4'-trithiobis(2,6-di-tert-butylphenol), 2,2'-thiobis(ethylenebis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]), 2,4-bis(n-octylthio)-6-(4-hydroxy-3',5'-di-tert-butylanilino)-1,3,5-triazine, N,N'-hexamethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamide), N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(3,5-di-tert-butyl-4-hydroxyphenyl) isocyanurate, tris(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 1,3,5-tris(4-tert-butyl-3-hydroxy-2,6-dimethylbenzyl) isocyanurate, 1,3,5-tris(2-[3(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxy]ethyl) isocyanurate, and tetrakis[methylene-3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane, etc. are exemplified. All of these are readily available.,
[0068] <Component E: Flame Retardant> The thermoplastic resin composition of the present invention contains a flame retardant as Component E. The blending of such a compound brings about an improvement in flame retardancy, but in addition, based on the properties of each compound, for example, improvements in antistatic properties, fluidity, rigidity, and thermal stability are also brought about. Such flame retardants include (i) halogen-based compounds, (ii) condensed phosphate ester compounds, (iii) phosphazene compounds, (iv) organic metal salts, and (v) inorganic compounds. These may be used alone or in combination of two or more kinds.,
[0069] (i) Halogen-based compounds Examples of the brominated flame retardant used in the present invention include brominated bisphenol A type polycarbonate flame retardants having a bromine content of 20% by weight or more, brominated bisphenol A type epoxy resins and modified products thereof in which the terminal glycidyl groups are partially or completely blocked, brominated diphenyl ether flame retardants, brominated imide flame retardants, brominated polystyrene flame retardants, and the like.
[0070] Specific examples include decabromodiphenyl oxide, octabromodiphenyl oxide, tetrabromodiphenyl oxide, tetrabromophthalic anhydride, hexabromocyclododecane, bis(2,4,6-tribromophenoxy)ethane, ethylene bistetrabromophthalimide, hexabromobenzene, 1,1-sulfonyl[3,5-dibromo-4-(2,3-dibromopropoxy)]benzene, polydibromophenylene oxide, tetrabromobisphenol S, tris(2,3-dibromopropyl-1)isocyanurate, tribromophenol, tribromophenyl allyl ether, tribromoneopentyl alcohol, brominated polystyrene, brominated polyethylene, tetrabromobisphenol A, tetrabromobisphenol A derivatives, tetrabromobisphenol A-epoxy ether ... oligomers or polymers, tetrabromobisphenol A-carbonate oligomers or polymers, brominated epoxy resins such as brominated phenol novolac epoxy, tetrabromobisphenol A-bis(2-hydroxydiethyl ether), tetrabromobisphenol A-bis(2,3-dibromopropyl ether), tetrabromobisphenol A-bis(allyl ether), tetrabromocyclooctane, ethylene bispentabromodiphenyl, tris(tribromoneopentyl)phosphate, poly(pentabromobenzyl polyacrylate), octabromotrimethylphenylindane, dibromoneopentyl glycol, pentabromobenzyl polyacrylate, dibromocresyl glycidyl ether, N,N'-ethylene-bis-tetrabromophthalimide, etc. Among them, tetrabromobisphenol A-epoxy oligomers, tetrabromobisphenol A-carbonate oligomers, brominated epoxy resins, etc. are mentioned.
[0071] Brominated polycarbonate (including oligomers) is particularly suitable as the brominated flame retardant of the present invention. Brominated polycarbonate has excellent heat resistance and can significantly improve flame retardancy. The brominated polycarbonate used in the present invention is a brominated polycarbonate compound in which the structural unit represented by the following general formula (8) accounts for at least 60 mol %, preferably at least 80 mol %, of all structural units, and particularly preferably substantially consists of the structural unit represented by the following general formula (8).
[0072] [ka]
[0073] (In the above general formula (8), X is a bromine atom, and R is an alkylene group having 1 to 4 carbon atoms, an alkylidene group having 1 to 4 carbon atoms, or -SO2-.) In the formula (8), R preferably represents a methylene group, an ethylene group, an isopropylidene group, or -SO2-, and particularly preferably an isopropylidene group.
[0074] The brominated polycarbonate has few residual chloroformate groups at its terminals, and the terminal chlorine content is preferably 0.3 ppm or less, more preferably 0.2 ppm or less. The terminal chlorine content can be determined by dissolving a sample in methylene chloride, adding 4-(p-nitrobenzyl)pyridine to react with the terminal chlorine (terminal chloroformate), and measuring the result with an ultraviolet-visible spectrophotometer (U-3200 manufactured by Hitachi, Ltd.). When the terminal chlorine content is 0.3 ppm or less, the thermal stability of the resin composition is improved, and molding at higher temperatures is possible, resulting in a resin composition with better molding processability.
[0075] In addition, the brominated polycarbonate preferably has few residual terminal hydroxyl groups. More specifically, the amount of terminal hydroxyl groups is preferably 0.0005 mol or less, more preferably 0.0003 mol or less, per mol of the constituent unit of the brominated polycarbonate. The amount of terminal hydroxyl groups is measured by dissolving a sample in deuterated chloroform and measuring the amount of terminal hydroxyl groups. 1This can be determined by measuring by H-NMR. Such an amount of terminal hydroxyl groups is preferable because the thermal stability of the resin composition is further improved.
[0076] The specific viscosity of the brominated polycarbonate is preferably in the range of 0.015 to 0.1, more preferably 0.015 to 0.08, and is calculated according to the above-mentioned formula for calculating the specific viscosity used in calculating the viscosity average molecular weight of the polycarbonate resin, which is the component A of the present invention.
[0077] The content of the halogen-based compound is 0.005 to 20 parts by weight, preferably 1 to 10 parts by weight, and more preferably 5 to 10 parts by weight, relative to 100 parts by weight of the resin component consisting of components A and B. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, yellowing during molding retention and resin deterioration in a high temperature and high humidity environment will increase.
[0078] (ii) Condensed phosphate ester compounds As the condensed phosphate ester compound, an aryl phosphate compound is preferably used. Condensed phosphate ester compounds have a plasticizing effect, and are therefore advantageous in that they can improve molding processability. As the aryl phosphate compound, various phosphate compounds known as flame retardants can be used, but more preferably, one or more phosphate compounds represented by the following general formula (9) can be used.
[0079] [ka]
[0080] (In the above general formula (9), M represents a divalent organic group derived from a dihydric phenol, and Ar 1 , Ar 2 , Ar 3 , and Ar 4Each of a, b, c, and d represents a monovalent organic group derived from a monohydric phenol. Each of a, b, c, and d is independently 0 or 1, and m is an integer of 0 to 5. In the case of a mixture of condensed phosphate esters having different degrees of polymerization m, m represents the average value thereof and is a value of 0 to 5.
[0081] The phosphate compound of the above formula may be a mixture of compounds having different m numbers, and in the case of such a mixture, the average m number is preferably in the range of 0.5 to 1.5, more preferably 0.8 to 1.2, even more preferably 0.95 to 1.15, and particularly preferably 1 to 1.14.
[0082] Specific preferred examples of the dihydric phenol from which M is derived include hydroquinone, resorcinol, bis(4-hydroxydiphenyl)methane, bisphenol A, dihydroxydiphenyl, dihydroxynaphthalene, bis(4-hydroxyphenyl)sulfone, bis(4-hydroxyphenyl)ketone, and bis(4-hydroxyphenyl)sulfide, and among these, resorcinol, bisphenol A, and dihydroxydiphenyl are preferred.
[0083] The above Ar 1 , Ar 2 , Ar 3 , and Ar 4 Preferred specific examples of the monohydric phenol from which the formula (I) is derived include phenol, cresol, xylenol, isopropylphenol, butylphenol, and p-cumylphenol, and among these, phenol and 2,6-dimethylphenol are preferred.
[0084] In addition, such monohydric phenols may be substituted with halogen atoms, and specific examples of phosphate compounds having a group derived from such monohydric phenols include tris(2,4,6-tribromophenyl)phosphate, tris(2,4-dibromophenyl)phosphate, and tris(4-bromophenyl)phosphate.
[0085] On the other hand, specific examples of phosphate compounds not substituted with halogen atoms include monophosphate compounds such as tri(2,6-xylyl)phosphate, as well as phosphate oligomers mainly made of resorcinol bis(di(2,6-xylyl)phosphate), phosphate oligomers mainly made of 4,4-dihydroxydiphenyl bis(diphenyl phosphate), and phosphoric ester oligomers mainly made of bisphenol A bis(diphenyl phosphate). (Here, "mainly made" means that it may contain small amounts of other components with different degrees of polymerization, and more preferably means that the component with m=1 in the above formula (9) is contained in an amount of 80% by weight or more, more preferably 85% by weight or more, and even more preferably 90% by weight or more.) The content of the condensed phosphate ester compound is 0.005 to 20 parts by weight, preferably 5 to 15 parts by weight, and more preferably 8 to 10 parts by weight, based on 100 parts by weight of the resin component consisting of components A and B. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, there is a decrease in heat resistance, yellowing during molding retention, and resin deterioration in a high-temperature and high-humidity environment becomes significant.
[0086] (iii) Phosphazene compounds Phosphazene compounds have a plasticizing effect, which is advantageous in that they can improve molding processability. As the phosphazene compound, various phosphazene compounds conventionally known as flame retardants can be used, but phosphazene compounds represented by the following general formulas (10) and (11) are preferred.
[0087] [ka]
[0088] [ka]
[0089] (In the formula, X 1 , X 2 , X 3 , X 4represents an organic group that does not contain hydrogen, a hydroxyl group, an amino group, or a halogen atom, and r represents an integer of 3 to 10.
[0090] In the above formulas (10) and (11), X 1 , X 2 , X 3 , X 4 Examples of the halogen-free organic group represented by the formula (10) include an alkoxy group, a phenyl group, an amino group, an allyl group, etc. Among these, the cyclic phosphazene compound represented by the formula (10) is preferred, and further, X 1 , X 2 Cyclic phenoxyphosphazenes in which is a phenoxy group are particularly preferred.
[0091] The content of the phosphazene compound is 0.005 to 20 parts by weight, preferably 2 to 10 parts by weight, and more preferably 3 to 7 parts by weight, based on 100 parts by weight of the resin component consisting of components A and B. If the content of the phosphazene compound is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, the heat resistance decreases, yellowing occurs during molding retention, and the resin deteriorates significantly in a high-temperature and high-humidity environment.
[0092] (iv) Organometallic salts The organic metal salt is preferably an alkali (earth) metal salt of an organic acid having 1 to 50 carbon atoms, preferably 1 to 40 carbon atoms, and is preferably an alkali (earth) metal salt of an organic sulfonate. The alkali (earth) metal salt of an organic sulfonate includes a metal salt of a fluorine-substituted alkylsulfonic acid, such as a metal salt of a perfluoroalkylsulfonic acid having 1 to 10 carbon atoms, preferably 2 to 8 carbon atoms, and an alkali metal or alkaline earth metal, and a metal salt of an aromatic sulfonic acid having 7 to 50 carbon atoms, preferably 7 to 40 carbon atoms, and an alkali metal or alkaline earth metal. Examples of the alkali metal constituting the metal salt include lithium, sodium, potassium, rubidium, and cesium, and examples of the alkaline earth metal include beryllium, magnesium, calcium, strontium, and barium. More preferred are alkali metals. Among these alkali metals, rubidium and cesium, which have a larger ionic radius, are preferred when a higher transparency is required, but these are not versatile and are difficult to purify, which may result in a disadvantage in terms of cost. On the other hand, metals with smaller ionic radii such as lithium and sodium may be disadvantageous in terms of flame retardancy. Taking these into consideration, the alkali metals in the alkali metal sulfonates can be selected appropriately, but in all respects, potassium sulfonates, which have an excellent balance of properties, are most suitable. Such potassium salts can also be used in combination with alkali metal sulfonates made of other alkali metals.
[0093] Specific examples of the alkali metal salt of perfluoroalkylsulfonate include potassium trifluoromethanesulfonate, potassium perfluorobutanesulfonate, potassium perfluorohexanesulfonate, potassium perfluorooctane sulfonate, sodium pentafluoroethanesulfonate, sodium perfluorobutanesulfonate, sodium perfluorooctane sulfonate, lithium trifluoromethanesulfonate, lithium perfluorobutanesulfonate, lithium perfluoroheptanesulfonate, cesium trifluoromethanesulfonate, cesium perfluorobutanesulfonate, cesium perfluorooctanesulfonate, cesium perfluorohexanesulfonate, rubidium perfluorobutanesulfonate, and rubidium perfluorohexanesulfonate, and the like, and these can be used alone or in combination of two or more. Here, the carbon number of the perfluoroalkyl group is preferably in the range of 1 to 18, more preferably in the range of 1 to 10, and even more preferably in the range of 1 to 8.
[0094] Among these, potassium perfluorobutanesulfonate is particularly preferred. Perfluoroalkylsulfonic acid alkali (earth) metal salts made of alkali metals usually contain a certain amount of fluoride ions (F-). The presence of such fluoride ions can be a factor in reducing flame retardancy, so it is preferable to reduce them as much as possible. The proportion of such fluoride ions can be measured by ion chromatography. The content of fluoride ions is preferably 100 ppm or less, more preferably 40 ppm or less, and particularly preferably 10 ppm or less. In terms of production efficiency, it is also preferable that the content is 0.2 ppm or more. Such perfluoroalkylsulfonic acid alkali (earth) metal salts with reduced amounts of fluoride ions can be produced by using known production methods, and by reducing the amount of fluoride ions contained in the raw materials when producing a fluorine-containing organometallic salt, by removing hydrogen fluoride and the like obtained by the reaction by heating or using gas generated during the reaction, and by reducing the amount of fluoride ions by using purification methods such as recrystallization and reprecipitation when producing a fluorine-containing organometallic salt. In particular, since organometallic salts are relatively soluble in water, it is preferable to produce them using ion-exchanged water, particularly water having an electric resistance of 18 MΩ·cm or more, i.e., an electric conductivity of about 0.55 μS / cm or less, and by dissolving and washing at a temperature higher than room temperature, followed by cooling and recrystallization.
[0095] Specific examples of the aromatic sulfonic acid alkali (earth) metal salts include disodium diphenyl sulfide-4,4'-disulfonate, dipotassium diphenyl sulfide-4,4'-disulfonate, potassium 5-sulfoisophthalate, sodium 5-sulfoisophthalate, polysodium polyethylene terephthalate polysulfonate, calcium 1-methoxynaphthalene-4-sulfonate, disodium 4-dodecylphenyl ether disulfonate, polysodium poly(2,6-dimethylphenylene oxide) polysulfonate, polysodium poly(1,3-phenylene oxide) polysulfonate, polysodium poly(1,4-phenylene oxide) polysulfonate, polypotassium poly(2,6-diphenylphenylene oxide) polysulfonate, lithium poly(2-fluoro-6-butylphenylene oxide) polysulfonate, potassium sulfonate of benzenesulfonate, sodium benzenesulfonate, and benzenesulfonic acid. Examples of the sulfonate include strontium, magnesium benzenesulfonate, dipotassium p-benzenedisulfonate, dipotassium naphthalene-2,6-disulfonate, calcium biphenyl-3,3'-disulfonate, sodium diphenylsulfone-3-sulfonate, potassium diphenylsulfone-3-sulfonate, dipotassium diphenylsulfone-3,3'-disulfonate, dipotassium diphenylsulfone-3,4'-disulfonate, sodium α,α,α-trifluoroacetophenone-4-sulfonate, dipotassium benzophenone-3,3'-disulfonate, disodium thiophene-2,5-disulfonate, dipotassium thiophene-2,5-disulfonate, calcium thiophene-2,5-disulfonate, sodium benzothiophenesulfonate, potassium diphenylsulfoxide-4-sulfonate, a formalin condensate of sodium naphthalenesulfonate, and a formalin condensate of sodium anthracenesulfonate. Of these alkali (earth) metal salts of aromatic sulfonic acid, potassium salts are particularly preferred.Among these alkali (earth) metal salts of aromatic sulfonates, potassium diphenylsulfone-3-sulfonate and dipotassium diphenylsulfone-3,3'-disulfonate are preferred, and a mixture thereof (wherein the weight ratio of the former to the latter is 15 / 85 to 30 / 70) is particularly preferred.
[0096] Suitable examples of organic metal salts other than alkali (earth) metal sulfonates include alkali (earth) metal salts of sulfates and alkali (earth) metal salts of aromatic sulfonamides. Examples of alkali (earth) metal salts of sulfates include alkali (earth) metal salts of sulfates of monohydric and / or polyhydric alcohols, and examples of sulfates of monohydric and / or polyhydric alcohols include methyl sulfate, ethyl sulfate, lauryl sulfate, hexadecyl sulfate, sulfate of polyoxyethylene alkylphenyl ether, mono-, di-, tri-, and tetrasulfate of pentaerythritol, sulfate of lauric acid monoglyceride, sulfate of palmitic acid monoglyceride, and sulfate of stearic acid monoglyceride. Examples of the alkali (earth) metal salts of these sulfates include alkali (earth) metal salts of lauryl sulfate. Examples of the alkali (earth) metal salt of aromatic sulfonamide include saccharin, N-(p-tolylsulfonyl)-p-toluenesulfonimide, N-(N'-benzylaminocarbonyl)sulfanilimide, and alkali (earth) metal salt of N-(phenylcarboxyl)sulfanilimide. The content of the organic metal salt is 0.005 to 20 parts by weight, preferably 0.005 to 1 part by weight, and more preferably 0.01 to 0.1 part by weight, relative to 100 parts by weight of the total of the A component and the B component. If the content is less than 0.005 parts by weight, it is difficult to obtain the effect of flame retardancy, and if it exceeds 20 parts by weight, yellowing during molding retention and resin deterioration under high temperature and high humidity environments will increase.
[0097] (v) Inorganic compounds Examples of the inorganic compounds include silicone compounds, fibril-forming fluorine-containing polymers and antimony compounds.
[0098] Silicone compounds improve flame retardancy by chemical reactions during combustion. As such compounds, various compounds that have been proposed as flame retardants for aromatic polycarbonate resins can be used. Silicone compounds are believed to impart high flame retardancy, particularly when used with polycarbonate resins, by forming a structure by bonding with themselves or with a component derived from the resin during combustion, or by a reduction reaction during the formation of the structure.
[0099] Therefore, it is preferable that the silicone-based compound contains a group having high activity in such a reaction, and more specifically, it is preferable that the silicone-based compound contains a predetermined amount of at least one group selected from an alkoxy group and a hydrogen (i.e., a Si-H group). The content ratio of such groups (alkoxy group, Si-H group) is preferably in the range of 0.1 to 1.2 mol / 100 g, more preferably in the range of 0.12 to 1 mol / 100 g, and even more preferably in the range of 0.15 to 0.6 mol / 100 g. The ratio is determined by measuring the amount of hydrogen or alcohol generated per unit weight of the silicone-based compound by an alkali decomposition method. The alkoxy group is preferably an alkoxy group having 1 to 4 carbon atoms, and in particular, a methoxy group is suitable.
[0100] Generally, the structure of a silicone compound is composed of any combination of the following four types of siloxane units: M unit: (CH3)3SiO 1 / 2 , H(CH3)2SiO 1 / 2 , H2(CH3)SiO 1 / 2 , (CH3)2(CH2=CH)SiO 1 / 2 , (CH3)2(C6H5)SiO 1 / 2 , (CH3)(C6H5)(CH2=CH)SiO 1 / 2D units: (CH3)2SiO, H(CH3)SiO, H2SiO, H(C6H5)SiO, (CH3)(CH2=CH)SiO, (C6H5)2SiO and other difunctional siloxane units; T units: (CH3)SiO 3 / 2 , (C3H7)SiO 3 / 2 , HSiO 3 / 2 , (CH2=CH)SiO 3 / 2 , (C6H5)SiO 3 / 2 and Q unit: a tetrafunctional siloxane unit represented by SiO2.
[0101] Specifically, the structure of the silicone compound used in the silicone flame retardant can be represented by the rational formula Dn, Tp, MmDn, MmTp, MmQq, MmDnTp, MmDnQq, MmTpQq, MmDnTpQq, DnTp, DnQq, and DnTpQq. Among these, preferred structures of the silicone compound are MmDn, MmTp, MmDnTp, and MmDnQq, and more preferred structures are MmDn and MmDnTp.
[0102] Here, the coefficients m, n, p, and q in the rational formula are integers of 1 or more that represent the degree of polymerization of each siloxane unit, and the sum of the coefficients in each rational formula is the average degree of polymerization of the silicone compound. This average degree of polymerization is preferably in the range of 3 to 150, more preferably in the range of 3 to 80, even more preferably in the range of 3 to 60, and particularly preferably in the range of 4 to 40. The more preferable the range, the better the flame retardancy. Furthermore, as described later, in a silicone-based compound containing a predetermined amount of aromatic groups, the transparency and hue are also excellent. As a result, good reflected light can be obtained. In addition, when any of m, n, p, and q is a value of 2 or more, the siloxane unit with the coefficient can be two or more kinds of siloxane units with different hydrogen atoms or organic residues bonded thereto.
[0103] The silicone compound may be linear or branched. The organic residue bonded to the silicone atom is preferably an organic residue having 1 to 30 carbon atoms, more preferably 1 to 20 carbon atoms. Specific examples of such organic residues include alkyl groups such as methyl, ethyl, propyl, butyl, hexyl, and decyl, cycloalkyl groups such as cyclohexyl, aryl groups such as phenyl, and aralkyl groups such as tolyl. More preferred are alkyl groups, alkenyl groups, and aryl groups having 1 to 8 carbon atoms. As the alkyl group, alkyl groups having 1 to 4 carbon atoms, such as methyl, ethyl, and propyl, are particularly preferred. Furthermore, the silicone compound used as the silicone flame retardant preferably contains an aryl group. On the other hand, the silane and siloxane compounds as the organic surface treatment agents for titanium dioxide pigments are clearly distinguished from silicone flame retardants in their preferred embodiments in that they are more effective when they do not contain an aryl group. The silicone compound used as the silicone flame retardant may contain a reactive group other than the Si-H group and the alkoxy group. Examples of such reactive groups include an amino group, a carboxyl group, an epoxy group, a vinyl group, a mercapto group, and a methacryloxy group.
[0104] The content of the silicon compound is 0.005 to 20 parts by weight, preferably 0.5 to 10 parts by weight, and more preferably 1 to 5 parts by weight, based on 100 parts by weight of the resin component consisting of components A and B. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, yellowing during molding retention and resin deterioration in a high temperature and high humidity environment will increase.
[0105] An example of a fibril-forming fluoropolymer is polytetrafluoroethylene (fibrillated PTFE). The fibrillated PTFE may be fibrillated PTFE alone or a mixed form of fibrillated PTFE, i.e., a polytetrafluoroethylene mixture consisting of fibrillated PTFE particles and an organic polymer. The fibrillated PTFE has an extremely high molecular weight, and tends to bond PTFE molecules together to form a fiber by an external action such as a shear force. The number average molecular weight is in the range of 1.5 million to tens of millions. The lower limit is more preferably 3 million. The number average molecular weight is calculated based on the melt viscosity of polytetrafluoroethylene at 380°C, as disclosed in, for example, JP-A-6-145520. That is, the fibrillated PTFE has a melt viscosity at 380°C of 10 7 ~10 13 The range is preferably 10 8 ~10 12 The range of poise. Such fibrillated PTFE can be used in the form of an aqueous dispersion in addition to a solid form. In addition, such fibrillated PTFE can be used in the form of a PTFE mixture mixed with other resins to improve dispersibility in resins and obtain better flame retardancy and mechanical properties.
[0106] Furthermore, as disclosed in Japanese Patent Application Laid-Open No. 6-145520, a structure having such fibrillated PTFE as a core and low molecular weight polytetrafluoroethylene as a shell is also preferably used.
[0107] Examples of commercially available products of such fibrillated PTFE include Teflon (registered trademark) 6J from Mitsui DuPont Fluorochemicals Co., Ltd., and Polyflon MPA FA500 and F-201L from Daikin Chemical Industries, Ltd.
[0108] The mixed form of fibrillated PTFE can be prepared by (1) mixing an aqueous dispersion of fibrillated PTFE with an aqueous dispersion or solution of an organic polymer and co-precipitating to obtain a coagulated mixture (methods described in JP-A-60-258263, JP-A-63-154744, etc.), (2) mixing an aqueous dispersion of fibrillated PTFE with dried organic polymer particles (method described in JP-A-4-272957), or (3) uniformly mixing an aqueous dispersion of fibrillated PTFE with a solution of organic polymer particles and extracting the fibrillated PTFE from the mixture. (4) a method of simultaneously removing the media from the fibrillated PTFE and the organic polymer in an aqueous dispersion of fibrillated PTFE (method described in JP-A-06-220210, JP-A-08-188653, etc.), (5) a method of uniformly mixing an aqueous dispersion of PTFE and an organic polymer dispersion, and then polymerizing a vinyl monomer in the mixed dispersion to obtain a mixture (method described in JP-A-11-29679, etc.).
[0109] Commercially available products of these mixed forms of fibrillated PTFE include the Metablen A series represented by "Metablen A3000" (product name), "Metablen A3700" (product name), and "Metablen A3800" (product name) manufactured by Mitsubishi Rayon Co., Ltd., SN3300B7 (product name) manufactured by Shine Polymer, and "BLENDEX B449" (product name) manufactured by GE Specialty Chemicals.
[0110] The ratio of fibrillated PTFE in the mixed form is preferably 1 wt% to 95 wt%, more preferably 10 wt% to 90 wt%, and most preferably 20 wt% to 80 wt%, of 100 wt% of the mixture.
[0111] When the ratio of fibrillated PTFE in the mixed form is within this range, good dispersibility of the fibrillated PTFE can be achieved. The content of the fibrillated PTFE is 0.005 to 20 parts by weight, preferably 0.01 to 0.5 parts by weight, and more preferably 0.1 to 0.5 parts by weight, relative to 100 parts by weight of the resin component consisting of components A and B. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, yellowing during retention in molding increases.
[0112] The antimony compound is preferably one that has been previously heat-treated at a temperature of 100° C. or higher, and preferably 300° C. or higher. If the antimony compound is not heated or if the antimony compound is heated at a temperature lower than 100° C., the molecular weight of the resulting resin composition may be significantly reduced, and a good molded product may not be obtained. This is thought to be because the crystal water or attached water of the antimony compound is released during the melt-kneading process, causing hydrolysis of the polycarbonate resin.
[0113] The content of the antimony compound is 0.005 to 20 parts by weight, preferably 0.5 to 10 parts by weight, and more preferably 1 to 5 parts by weight, based on 100 parts by weight of the resin component consisting of components A and B. If the content is less than 0.005 parts by weight, it is difficult to obtain a flame retardant effect, and if it exceeds 20 parts by weight, yellowing during molding retention and resin deterioration in a high temperature and high humidity environment will increase.
[0114] (Other additives) In the thermoplastic resin composition of the present invention, additives used for improving the thermal stability and designability can be advantageously used. These additives will be specifically described below. (I) Heat stabilizer (i) Heat stabilizers other than those mentioned above The thermoplastic resin composition of the present invention may also contain other heat stabilizers than the orthophosphate compounds and phenol compounds. Suitable examples of such other heat stabilizers include lactone stabilizers, such as the reaction product of 3-hydroxy-5,7-di-tert-butyl-furan-2-one and o-xylene. Details of such stabilizers are described in JP-A-7-233160. Such a compound is commercially available as Irganox HP-136 (trademark, manufactured by CIBA SPECIALTY CHEMICALS), and this compound can be used. Furthermore, stabilizers in which this compound is mixed with various orthophosphate compounds and hindered phenol compounds are commercially available. Suitable examples include Irganox HP-2921 manufactured by the same company. The content of the lactone stabilizer is preferably 0.0005 to 0.05 parts by weight, more preferably 0.001 to 0.03 parts by weight, based on 100 parts by weight of the resin component consisting of the A component and the B component. Other examples of the stabilizer include sulfur-containing stabilizers such as pentaerythritol tetrakis (3-mercaptopropionate), pentaerythritol tetrakis (3-laurylthiopropionate), and glycerol-3-stearylthiopropionate. The content of such sulfur-containing stabilizers is preferably 0.001 to 0.1 parts by weight, more preferably 0.01 to 0.08 parts by weight, based on 100 parts by weight of the resin component consisting of the A component and the B component. An epoxy compound can be blended into the thermoplastic resin composition of the present invention as necessary. Such an epoxy compound is blended for the purpose of suppressing mold corrosion, and basically all compounds having an epoxy functional group can be applied. Specific examples of preferred epoxy compounds include 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexylcarboxylate, 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, copolymers of methyl methacrylate and glycidyl methacrylate, and copolymers of styrene and glycidyl methacrylate.The content of such an epoxy compound is preferably 0.003 to 0.2 parts by weight, more preferably 0.004 to 0.15 parts by weight, and even more preferably 0.005 to 0.1 parts by weight, based on 100 parts by weight of the resin component consisting of the A component and the B component.
[0115] (II) Dyes and pigments The thermoplastic resin composition of the present invention further contains various dyes and pigments, and can provide molded products that exhibit a variety of designs. Examples of dyes and pigments used in the present invention include perylene dyes, coumarin dyes, thioindigo dyes, anthraquinone dyes, thioxanthone dyes, ferrocyanides such as Prussian blue, perinone dyes, quinoline dyes, quinacridone dyes, dioxazine dyes, isoindolinone dyes, and phthalocyanine dyes. Furthermore, the thermoplastic resin composition of the present invention can be blended with a metallic pigment to obtain a better metallic color. Aluminum powder is suitable as the metallic pigment. In addition, by blending a fluorescent brightener or other fluorescent dye that emits light, a better design effect that makes use of the luminous color can be imparted.
[0116] (III) Fluorescent whitening agents In the thermoplastic resin composition of the present invention, the fluorescent brightener is not particularly limited as long as it is used to improve the color tone of the resin or the like to white or bluish white, and examples thereof include stilbene-based, benzimidazole-based, benzoxazole-based, naphthalimide-based, rhodamine-based, coumarin-based, and oxazine-based compounds. Specific examples include CI Fluorescent Brightener 219:1, Eastman Chemical Company's EASTOBRITE OB-1, and Showa Chemical Company's "HAKKOL PSR." Here, the fluorescent brightener has the effect of absorbing ultraviolet energy of light and radiating this energy in the visible region. The content of the fluorescent brightener is preferably 0.001 to 0.1 parts by weight, more preferably 0.001 to 0.05 parts by weight, based on 100 parts by weight of the resin component consisting of the A component and the B component. Even if the content exceeds 0.1 part by weight, the effect of improving the color tone of the composition is small.
[0117] (IV) Compounds capable of absorbing heat rays The thermoplastic resin composition of the present invention may contain a compound having heat absorbing ability. Suitable examples of such compounds include phthalocyanine-based near infrared absorbing agents, metal oxide-based near infrared absorbing agents such as ATO, ITO, iridium oxide, ruthenium oxide, immonium oxide, and titanium oxide, various metal compounds having excellent near infrared absorbing ability such as metal boride-based and tungsten oxide-based near infrared absorbing agents such as lanthanum boride, cerium boride, and tungsten boride, and carbon fillers. As such phthalocyanine-based near infrared absorbing agents, for example, MIR-362 manufactured by Mitsui Chemicals, Inc. is commercially available and easily available. Examples of carbon fillers include carbon black, graphite (both natural and artificial), and fullerene, and preferably carbon black and graphite. These can be used alone or in combination of two or more. The content of the phthalocyanine-based near infrared absorbing agent is preferably 0.0005 to 0.2 parts by weight, more preferably 0.0008 to 0.1 parts by weight, and even more preferably 0.001 to 0.07 parts by weight, relative to 100 parts by weight of the resin component consisting of components A and B. The contents of the metal oxide-based near infrared absorbing agent, metal boride-based near infrared absorbing agent, and carbon filler are preferably in the range of 0.1 to 200 ppm (weight ratio), and more preferably in the range of 0.5 to 100 ppm, in the thermoplastic resin composition of the present invention.
[0118] (V) Light diffusing agent The thermoplastic resin composition of the present invention can be blended with a light diffusing agent to impart a light diffusing effect. Examples of such light diffusing agents include polymer fine particles, inorganic fine particles with a low refractive index such as calcium carbonate, and composites thereof. Such polymer fine particles are fine particles already known as light diffusing agents for polycarbonate resins. More preferred examples include acrylic crosslinked particles with a particle size of several μm and silicone crosslinked particles represented by polyorganosilsesquioxane. Examples of the shape of the light diffusing agent include spherical, discoid, columnar, and indefinite shapes. Such a sphere does not need to be a perfect sphere and includes deformed ones, and such a columnar shape includes a cube. A preferred light diffusing agent is spherical, and the more uniform the particle size, the more preferred it is. The content of the light diffusing agent is preferably 0.005 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, and even more preferably 0.01 to 3 parts by weight, based on 100 parts by weight of the resin component consisting of the A component and the B component. Two or more types of light diffusing agents can be used in combination.
[0119] (VI) Highly light-reflecting white pigments The thermoplastic resin composition of the present invention can be blended with a highly light-reflective white pigment to impart a light-reflecting effect. Titanium dioxide (particularly titanium dioxide treated with an organic surface treatment agent such as silicone) pigment is particularly preferred as such a white pigment. The content of such highly light-reflective white pigment is preferably 3 to 30 parts by weight, more preferably 8 to 25 parts by weight, based on 100 parts by weight of the resin component consisting of components A and B. Two or more types of highly light-reflective white pigments can be used in combination.
[0120] (VII) Ultraviolet absorbers The thermoplastic resin composition of the present invention can be blended with an ultraviolet absorbing agent to impart weather resistance.Specific examples of such ultraviolet absorbing agents include benzophenone-based agents such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxy-5-sodiumsulfoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, 2-hydroxy-4-n-dodecyloxybenzophenone, and 2-hydroxy-4-methoxy-2'-carboxybenzophenone.Specific examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers such as 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dicumylphenyl)phenylbenzotriazole, 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(2-hydroxy-3,5-di-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-3,5-di-tert-amylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, Examples of the copolymer include 2-hydroxyphenyl-2H-benzotriazole skeleton such as 2-(2-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)-benzotriazole, 2-(2-hydroxy-4-octoxyphenyl)-benzotriazole, 2,2'-methylenebis(4-cumyl-6-benzotriazolephenyl), 2,2'-p-phenylenebis(1,3-benzoxazin-4-one), and 2-[2-hydroxy-3-(3,4,5,6-tetrahydrophthalimidomethyl)-5-methylphenyl]benzotriazole, and copolymers of 2-(2'-hydroxy-5-methacryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer, and copolymers of 2-(2'-hydroxy-5-acryloxyethylphenyl)-2H-benzotriazole and vinyl monomers copolymerizable with the monomer.Specific examples of the ultraviolet absorber include, in the hydroxyphenyltriazine series, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-hexyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-methyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-ethyloxyphenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-propyloxyphenol, and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-butyloxyphenol.Further examples include compounds in which the phenyl group of the above-mentioned compounds is a 2,4-dimethylphenyl group, such as 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hexyloxyphenol. Specific examples of the ultraviolet absorbent include cyclic iminoesters such as 2,2'-p-phenylenebis(3,1-benzoxazine-4-one), 2,2'-m-phenylenebis(3,1-benzoxazine-4-one), and 2,2'-p,p'-diphenylenebis(3,1-benzoxazine-4-one). Specific examples of the ultraviolet absorbent include cyanoacrylates such as 1,3-bis-[(2'-cyano-3',3'-diphenylacryloyl)oxy]-2,2-bis[(2-cyano-3,3-diphenylacryloyl)oxy]methyl)propane and 1,3-bis-[(2-cyano-3,3-diphenylacryloyl)oxy]benzene. Furthermore, the ultraviolet absorber may be a polymer type ultraviolet absorber obtained by copolymerizing such an ultraviolet absorbing monomer and / or a light stable monomer with a monomer such as an alkyl (meth)acrylate by adopting a structure of a radically polymerizable monomer compound. Suitable examples of the ultraviolet absorbing monomer include compounds containing a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, a cyclic imino ester skeleton, and a cyanoacrylate skeleton in the ester substituent of a (meth)acrylic acid ester.Among the above, benzotriazole and hydroxyphenyltriazine are preferred in terms of ultraviolet absorbing ability, and cyclic iminoester and cyanoacrylate are preferred in terms of heat resistance and color. Specific examples include "Chemisorb 79" from Chemipro Kasei Co., Ltd. and "Tinuvin 234" from BASF Japan Co., Ltd. The ultraviolet absorbing agents may be used alone or in a mixture of two or more kinds.
[0121] The content of the ultraviolet absorber is preferably 0.01 to 3 parts by weight, more preferably 0.01 to 1 part by weight, still more preferably 0.05 to 1 part by weight, and particularly preferably 0.05 to 0.5 parts by weight, relative to 100 parts by weight of the resin component consisting of components A and B.
[0122] (VIII) Antistatic agents The thermoplastic resin composition of the present invention may be required to have antistatic properties, and in such a case, it is preferable to include an antistatic agent. Examples of such antistatic agents include (1) organic sulfonate phosphonium salts such as arylsulfonate phosphonium salts, typified by dodecylbenzenesulfonate phosphonium salts, and alkylsulfonate phosphonium salts, as well as borate phosphonium salts such as tetrafluoroborate phosphonium salts. The content of the phosphonium salt is appropriately 5 parts by weight or less, preferably 0.05 to 5 parts by weight, more preferably 1 to 3.5 parts by weight, and even more preferably 1.5 to 3 parts by weight, relative to 100 parts by weight of the components consisting of the A component and the B component. Examples of the antistatic agent include (2) organic sulfonate alkali (earth) metal salts such as lithium organic sulfonate, sodium organic sulfonate, potassium organic sulfonate, cesium organic sulfonate, rubidium organic sulfonate, calcium organic sulfonate, magnesium organic sulfonate, and barium organic sulfonate. As mentioned above, such metal salts are also used as flame retardants. More specifically, such metal salts include metal salts of dodecylbenzenesulfonic acid and metal salts of perfluoroalkanesulfonic acid. The content of the alkali (earth) metal salt of organic sulfonate is suitably 0.5 parts by weight or less, preferably 0.001 to 0.3 parts by weight, and more preferably 0.005 to 0.2 parts by weight, per 100 parts by weight of the resin component consisting of components A and B. In particular, alkali metal salts such as potassium, cesium, and rubidium are suitable.
[0123] Examples of the antistatic agent include (3) organic ammonium sulfonate salts such as ammonium alkylsulfonate salts and ammonium arylsulfonate salts. The amount of the ammonium salt is preferably 0.05 parts by weight or less per 100 parts by weight of the component consisting of components A and B. Examples of the antistatic agent include (4) polymers containing a poly(oxyalkylene) glycol component as a constituent component, such as polyether ester amide. The amount of the polymer is preferably 5 parts by weight or less per 100 parts by weight of the resin component consisting of components A and B.
[0124] (IX) Filler The thermoplastic resin composition of the present invention can be blended with various fillers known as reinforcing fillers other than fibrous fillers. As such fillers, various plate-like fillers and granular fillers can be used. Here, the plate-like filler is a filler having a plate shape (including those having an uneven surface and those having a curved plate). The granular filler is a filler having a shape other than these, including an irregular shape.
[0125] Preferred examples of the plate-like filler include glass flakes, talc, mica, kaolin, metal flakes, carbon flakes, and graphite, as well as plate-like fillers obtained by surface-coating these fillers with different materials such as metals and metal oxides. The particle size is preferably in the range of 0.1 to 300 μm. The particle size refers to the value of the median diameter (D50) of the particle size distribution measured by the X-ray transmission method, which is one of the liquid phase precipitation methods, in the region up to about 10 μm, the value of the median diameter (D50) of the particle size distribution measured by the laser diffraction / scattering method in the region of 10 to 50 μm, and the value of the vibration sieving method in the region of 50 to 300 μm. The particle size is the particle size in the resin composition. The plate-like filler may be surface-treated with various coupling agents such as silane-, titanate-, aluminate-, and zirconate-based coupling agents, or may be in the form of granules that have been bundled or compressed with various resins such as olefin-, styrene-, acrylic-, polyester-, epoxy-, and urethane-based resins, or higher fatty acid esters.
[0126] (X) Other resins and elastomers In the thermoplastic resin composition of the present invention, other resins or elastomers may be used in small proportions in place of a part of the resin components, as long as the effects of the present invention are not impaired. The amount of the other resins or elastomers is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, even more preferably 5 parts by weight or less, and most preferably 3 parts by weight or less, based on 100 parts by weight of the resin components consisting of components A and B. Examples of such other resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, silicone resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polymethacrylate resins, phenolic resins, and epoxy resins. Examples of elastomers include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber, MB (methyl methacrylate / butadiene) rubber, and MAS (methyl methacrylate / acrylonitrile / styrene) rubber.
[0127] (XI) Other Additives The thermoplastic resin composition of the present invention may also contain other flow modifiers, antibacterial agents, dispersants such as liquid paraffin, photocatalytic antifouling agents, photochromic agents, and the like.
[0128] <Production of Resin Composition> The thermoplastic resin composition of the present invention can be pelletized by melt kneading using an extruder such as a single screw extruder or a twin screw extruder. When preparing such pellets, the above-mentioned various reinforcing fillers and additives can also be blended.
[0129] <Regarding the manufacturing of molded products> The thermoplastic resin composition of the present invention can be used to produce various products by injection molding the pellets produced as described above. Furthermore, it is also possible to directly produce sheets, films, irregular extrusion molded products, direct blow molded products, and injection molded products from the resin melt-kneaded in an extruder without passing through pellets. In such injection molding, molded products can be obtained using injection molding methods such as injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and ultra-high speed injection molding, in addition to ordinary molding methods, depending on the purpose. The advantages of these various molding methods are already widely known. In addition, either the cold runner method or the hot runner method can be selected for molding. The resin composition of the present invention can also be used in the form of various irregular extrusion molded products, sheets, and films by extrusion molding. In addition, the inflation method, calendar method, casting method, and the like can be used for molding sheets and films. Furthermore, it is also possible to mold the resin composition into a heat-shrinkable tube by subjecting it to a specific stretching operation. The resin composition of the present invention can also be formed into molded articles by rotational molding, blow molding, or the like. Effect of the Invention
[0130] The thermoplastic resin composition of the present invention has excellent heat resistance and flame retardancy, does not discolor during molding dwell, and furthermore, is inhibited from resin deterioration under high temperature and high humidity environments. Therefore, the composition is useful for various applications such as electric and electronic parts, home appliances, automobile-related parts, infrastructure-related parts, housing-related parts, medical instruments and devices, and the industrial effects thereof are exceptional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0131] The embodiments of the present invention are those that summarize the preferred ranges of the above-mentioned requirements, and representative examples are described in the following examples, although the present invention is not limited to these embodiments. EXAMPLES
[0132] The present invention will be further described below with reference to examples. In the examples, parts are by weight and % is by weight unless otherwise specified. Evaluations were performed by the following methods.
[0133] (Evaluation of Thermoplastic Resin Composition) (i) Deflection temperature under load Using the ISO bending test pieces obtained by the following method, the deflection temperature under load (load: 0.45 MPa) was measured according to ISO 75-1 and ISO 75-2. The deflection temperature under load of the resin composition of the present invention must be 145°C or higher.
[0134] (ii) Flame retardancy Tests were conducted using test pieces with thicknesses of 0.5 mm, 1.0 mm, and 1.5 mm prepared according to the UL94 standard using the following method. Based on the test results, the test pieces were rated as UL-94 V-0, V-1, V-2, or Not-V. The flame retardancy of the resin composition of the present invention must be V-0 for test pieces with thicknesses of 0.5 mm, 1.0 mm, or 1.5 mm.
[0135] (iii) ΔMw (change in viscosity average molecular weight) The viscosity average molecular weight (Mw) is calculated by the specific viscosity (η SP ) was measured at 20°C using an Ostwald viscometer from a solution prepared by dissolving 0.7 g of the sample plate obtained by the method described below in 100 ml of methylene chloride. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] The specific viscosity (η SP ) was calculated using the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 Mw 0.83 c=0.7 Next, ΔMw was calculated from the Mw obtained by the above measurement method according to the following formula. ΔMw=Mw1-Mw2 Mw1: Viscosity average molecular weight of the sample plate obtained by the following method before testing Mw2: Viscosity average molecular weight after 20 hours of testing under 130℃ / 100% environment using a highly accelerated life tester (ESPEC EHS-412MD) of the sample plate obtained by the following method
[0136] (iv) ΔYI Using the method described below, a sample board with a side length of 50 mm and a thickness of 3 mm was molded continuously from the 1st shot to the 15th shot, and after 10 minutes of molding was stopped, the 16th and 17th shots were molded continuously. ΔYI was calculated using the following formula. The YI value was measured using a color tone measuring device (Nippon Denshoku SE-2000 colorimeter) based on JIS K7103. ΔYI = YI2 - YI1 YI1: YI value of the molded product after the 8th shot YI2: YI value of the molded product after the 17th shot
[0137] (B component) [Production of polyarylate resin (B-1)] Into a reaction vessel equipped with a stirring vessel, 8.2 kg (36 mol) of 2,2-bis(4-hydroxyphenyl)propane, 11.1 kg (36 mol) of 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 3.4 kg (18 mol) of 4,4-dihydroxy-biphenyl as dihydric phenol residues, 670 g (4.4 mol) of p-tert-butylphenol (hereinafter sometimes abbreviated as PTBP) (PTBP manufactured by DIC Corporation) as a molecular weight regulator, 8.6 kg (213 mol) of sodium hydroxide (manufactured by Tosoh Corporation) as an alkali, 373 g of benzyl-tri-n-butylammonium chloride (hereinafter sometimes abbreviated as BTBAC) (BTBAC-50 manufactured by Lion Akzo Corporation) as a polymerization catalyst, and 107 g of sodium hydrosulfite (hereinafter sometimes abbreviated as SHS) (manufactured by BASF Corporation) were poured, and 400 L of water was poured into the reaction vessel to dissolve the dihydric phenol residues, forming an aqueous phase.
[0138] Further, in another reaction vessel, 18.6 kg (91 moles) of mixed phthalic acid chloride (MPC manufactured by Ihara Nikkei Chemical Industry Co., Ltd.; terephthalic acid / isophthalic acid = 50 / 50 (mass%)) was dissolved in 240 L of dichloromethylene (methylene chloride manufactured by Tokuyama Corporation) to obtain an organic phase. This organic phase was added to the aqueous phase already being stirred under strong stirring, and the temperature was kept at 15°C to carry out a polymerization reaction for 2 hours. After this, stirring was stopped, and the aqueous phase and the organic phase were separated by decantation. 400 L of pure water and 100 mL of acetic acid were added to the organic phase from which the aqueous phase had been removed to stop the reaction, and the mixture was further stirred at 15°C for 30 minutes. This organic phase was washed five times with pure water, and the organic phase was added to 400 L of hexane to precipitate a polymer. The precipitated polymer was separated from the organic phase and then dried to obtain a polyarylate resin (B-1). Regarding the obtained polyarylate resin (B-1) 1 Composition analysis was performed using H-NMR (ECA500 NMR manufactured by JEOL Ltd.), and it was confirmed that the polymerization ratio of dihydric phenol residues to phthalic acid residues was 1:1, which was the same as the mixing ratio of dihydric phenol residues to phthalic acid residues. In addition, the viscosity average molecular weight of the obtained polyarylate resin was 19,300. The results are shown in Table 1.
[0139] [Production of polyarylate resins (B-2, B-3)] [Polyarylate resin (B-2)] and [Polyarylate resin (B-3)] were obtained in the same manner as in [Production of polyarylate resin (B-1)], except that the blending amounts of dihydric phenol and aromatic dicarboxylic acid were as shown in Table 1. The viscosity average molecular weights of the obtained polyarylate resins were 21,800 and 60,000, respectively. The results are shown in Table 1.
[0140] The symbols used for each component in Table 1 are as follows: (Aromatic dicarboxylic acids) TP: Terephthalic acid IP: Isophthalic acid (Dihydric phenol) BPA: Bisphenol A [2,2-bis(4-hydroxyphenyl)propane] BPTMC: Bisphenol TMC [bisphenol 3,3,5-trimethylcyclohexane] BP: Biphenol [4,4-dihydroxy-biphenyl]
[0141] (Examples 1 to 14, Comparative Examples 1 to 10) A mixture of the compositions shown in Tables 2 and 3 was fed from the first feed port of the extruder. Such a mixture was obtained by mixing with a V-type blender. The twin-screw extruder used was a "TEX30αIII" intermeshing co-rotating twin-screw extruder manufactured by Japan Steel Works, Ltd., with a diameter of 30 mmφ and a total of 10 barrels (referred to as C1 to C10 cylinders from the upstream) with a feed port at the most upstream C1 and at C5 downstream of the same, and one vent. The extrusion conditions were temperature C1: 300°C, C2 to 10: 310°C, screw rotation speed 200 rpm, discharge rate 25 kg / h, and vent vacuum degree 3 kPa, and pellets were obtained by melt mixing.
[0142] A portion of the resulting pellets was dried in a hot air circulation dryer at 120°C for 6 hours, and then molded using an injection molding machine at a cylinder temperature of 320°C and a mold temperature of 90°C into sample plates with a side length of 50 mm and a thickness of 3 mm, ISO bending test pieces (compliant with ISO 75-1 and 75-2), and UL94 test pieces for evaluation, and each evaluation was performed. The evaluation results are shown in Tables 2 and 3. The components represented by symbols in Tables 2 and 3 are as follows:
[0143] (Component A) A-1: Aromatic polycarbonate resin (polycarbonate resin powder with a viscosity average molecular weight of 22,400 made by a conventional method from bisphenol A and phosgene, manufactured by Teijin Ltd., Panlite L-1225WP (product name)) (B component) B-1: Resin synthesized in [Production of polyarylate resin (B-1)] B-2: Resin synthesized in [Production of polyarylate resin (B-2)] B-3: Resin synthesized in [Production of polyarylate resin (B-3)] (C component) C-1: Trimethyl phosphate (TMP, manufactured by Daihachi Chemical Industry Co., Ltd., number average molecular weight 140) C-2: 3,9-bis(2,6-di-tert-butyl-4-methylphenoxy)-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5,5]undecane (ADEKA PEP36, number average molecular weight 633) C-3: Tris(2,4-di-tert-butylphenyl)phosphite (Adeka 2112, number average molecular weight 647) (D component) D-1: Octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (AO-50 manufactured by Adeka) D-2: 3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1,-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane (AO-80 manufactured by Adeka) (E component) E-1: Halogen-based compounds (Teijin Limited, FG-7000) E-2: Condensed phosphate ester compound (PX-200, manufactured by Daihachi Chemical Industry Co., Ltd.) E-3: Phosphazene (FP-100 manufactured by Fushimi Seisakusho Co., Ltd.) E-4: Potassium perfluoroalkanesulfonate (F-114P, manufactured by Dainippon Ink and Chemicals, Inc.) E-5: Antimony trioxide (PATOX-K, manufactured by Nihon Seiko Co., Ltd.) E-6: Organic siloxane compound (X-40-2600J, manufactured by Shin-Etsu Chemical Co., Ltd.) E-7: Polytetrafluoroethylene (Polyflon MPAFA-500 manufactured by Daikin Chemical Industries, Ltd.)
[0144] [Table 1]
[0145] [Table 2]
[0146]
Table 3
Claims
1. A thermoplastic resin composition comprising 100 parts by weight of a resin component consisting of 1 to 99 parts by weight of (A) a polycarbonate resin (component A) and 99 to 1 part by weight of (B) a polyarylate resin (component B), and containing 0.001 to 0.02 parts by weight of (C) an orthophosphate compound (component C), 0.001 to 0.05 parts by weight of (D) a phenolic compound (component D), and 0.005 to 20 parts by weight of (E) a flame retardant (component E).
2. The thermoplastic resin composition according to claim 1, characterized in that component E contains at least one compound selected from the group consisting of halogen-based compounds, condensed phosphate ester compounds, phosphazene compounds, organic metal salts, inorganic compounds and fibril-forming fluorine-containing polymers.
3. 3. The thermoplastic resin composition according to claim 2, wherein the organometallic salt is a metal salt of a perfluoroalkanesulfonic acid.
4. 3. The thermoplastic resin composition according to claim 2, wherein the inorganic compound is at least one compound selected from the group consisting of silicon compounds and antimony compounds.
5. 5. The thermoplastic resin composition according to claim 1, wherein component D is a hindered phenol-based antioxidant.
6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein the component B is a polyarylate resin containing a polymerization unit represented by any one of the following general formulas (1) to (3): 【Chemistry 1】 (In the above general formula (1), l, m, and n are positive integers that satisfy l+m+n=100, l:n=50:50 to 70:30, and (l+n):m=75:25 to 40:60.) 【Chemistry 2】 (In the above general formula (2), m and n are positive integers, and m / n=8 / 2 to 2 / 8.) 【Chemistry 3】 (In the above general formula (3), n is a positive integer.)
7. 7. The thermoplastic resin composition according to claim 1, wherein the melting point of component D is 30 to 70° C.
8. 8. The thermoplastic resin composition according to claim 1, wherein the number average molecular weight of component C is 50 to 600.
9. A molded article obtained by molding the thermoplastic resin composition according to any one of claims 1 to 8.
Citation Information
Patent Citations
Resin coiposition
JP1993156147A
Light diffusible aromatic polycarbonate resin composition
JP2001323149A
Method and apparatus for applying paste
JP2002204058A
Flame-retardant resin composition
JP2006273931A
Molded article composed of aromatic polycarbonate resin composition
JP2009179784A